PAM‐SMEs: process assessment method for small to medium enterprises. Issue 8 (19th June 2016) - Abushama, Hisham M.
Abstract: Several software process improvement (SPI) standard models have been invented since the last decades, for example, CMMI, SPICE, and CMM. Most of these models had to be tailored by several researchers in order to be applied within Small to Medium Enterprises (SMEs). This is mainly due to their environmental challenges such as resources. In addition to this, the SPI models including the current standard model the CMMI are not considering tailoring their SPI program to business objectives. Achieving business objectives is the main recipe for business success. Therefore, this research (PAM‐SMEs) is setup to tailor SPI program to business objectives within SMEs environmental challenges. Key features of the PAM‐SMEs are as follows: the use of simplified and tailorable assessment techniques and data collection tool based on the CMMI; and then prioritizing the outcome of the assessment to the SMEs business objectives by the use of prioritization technique. The PAM‐SMEs was applied within three partner SMEs, and the overall evaluation shows that the PAM‐SMEs help to drive their SPI program toward their business objectives with the available resources. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : PAM‐SMEs is an assesment method for software process improvement (SPI) helping small to medium enterprises (SMEs) to tailor their SPI program to business objectives with respect to their resources limitiation. All SMEs research partner demonstrated that the capability of PAM‐SMEs to align SPI activities to business objectives and optimized with their resources limitation.